2020
DOI: 10.3892/ijmm.2020.4582
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamaldehyde protects against oxidative stress and inhibits the TNF‑α‑induced inflammatory response in human umbilical vein endothelial cells

Abstract: Oxidative stress and inflammation play critical roles in the development of cardiovascular diseases. Cinnamaldehyde (CA) is a natural compound from Cinnamomum cassia, and its anticancer, antimicrobial and anti-inflammatory activities have been widely investigated. In the present study, the cytoprotective and anti-inflammatory effects of CA on H 2 O 2-or tumor necrosis factor (TNF)-α-exposed human umbilical vein endothelial cells (HUVECs) were examined. CA and its natural derivative, 2-methoxycinnamaldehyde (MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…In addition, CINM also activates Nrf2, and this effect could be blocked by siRNA against Nrf2. These results suggest that CINM exerts protective effects on H 2 O 2 -induced HUVECs through the Nrf2/HO-1 signaling pathway [87] . Ferulic acid and caffeic acid are two other classical and simple phenylpropanoids that comprehensively exist in natural plants, and the two compounds possess similar structures.…”
Section: Protective Effects Of Herbal Medicine and Its Monomers On Vascular Endothelial Cells Related To Nrf2/ho-1mentioning
confidence: 69%
“…In addition, CINM also activates Nrf2, and this effect could be blocked by siRNA against Nrf2. These results suggest that CINM exerts protective effects on H 2 O 2 -induced HUVECs through the Nrf2/HO-1 signaling pathway [87] . Ferulic acid and caffeic acid are two other classical and simple phenylpropanoids that comprehensively exist in natural plants, and the two compounds possess similar structures.…”
Section: Protective Effects Of Herbal Medicine and Its Monomers On Vascular Endothelial Cells Related To Nrf2/ho-1mentioning
confidence: 69%
“…109 Cinnamaldehyde elevated the cellular protein level of HO-1 and facilitated the translocation of Nrf2 to the nucleus in HUVECs, which indicated that Nrf2/HO-1 may be the pathway by which cinnamaldehyde protects against oxidative stress. 17 In mouse aortas under high glucose conditions, cinnamaldehyde exerts antioxidant effects mediated through Nrf2 activation and the upregulation of downstream target proteins, including HO-1, NQO1, CAT, and glutathione peroxidase 1 (Gpx-1). 74 In short, the anti-atherosclerotic effects of cinnamon can also be explained by its antioxidative properties.…”
Section: Reviewmentioning
confidence: 99%
“…Numerous studies have revealed that cinnamon has neuroprotective, lipid-lowering, antioxidant, anti-inflammatory, and hypoglycaemic effects, some of which are closely related to the development of diabetes and CVDs. [13][14][15][16][17][18] In this review, we provide a comprehensive overview of the therapeutic potential and possible mechanisms of cinnamon in treating diabetes and CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…Uchi et al found that cinnamaldehyde can activate Nrf2 and induce its nuclear translocation, resulting in the upregulation of HO-1 gene expression [ 38 ]. Cinnamaldehyde also activates the Nrf2/HO-1 antioxidant system and was found to alleviate benzopyrene-induced ROS production in keratinocytes [ 39 , 40 ]. More than a hundred Kampo formulations, including cinnamaldehyde, have been approved by the Japanese Ministry of Health as prescription drugs for the treatment of various chronic diseases; cinnamaldehyde, in particular, may have the potential to treat vitiligo and other diseases caused by oxidative stress [ 38 , 41 ].…”
Section: Oxidative Stress and Vitiligomentioning
confidence: 99%